2014
DOI: 10.1108/f-10-2012-0078
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of facilities management as an academic discipline

Abstract: To what extent are the general requirements met and what does it mean? Abstract (250 words)Purpose -The purpose of this paper is to explore what an academic discipline is and to apply and discuss this definition using facilities management as an example. The paper addresses an academic world that is facing the challenge of developing research and education in response to emerging disciplines and dealing with changes in the higher education system. Institutions are also confronted with the aim of the European C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…The experienced author of this article attended the first European FM conference in Glasgow in 1990, which recognised and established a tradition for the development of FM as a profession, and as an academic discipline. Recently, Junghans and Olsson (2014) assessed the development of FM as an academic discipline, focusing on the aspects included in the knowledge triangle, and found that FM appeared to be on its way to becoming an established discipline.…”
Section: Methodology and Frameworkmentioning
confidence: 99%
“…The experienced author of this article attended the first European FM conference in Glasgow in 1990, which recognised and established a tradition for the development of FM as a profession, and as an academic discipline. Recently, Junghans and Olsson (2014) assessed the development of FM as an academic discipline, focusing on the aspects included in the knowledge triangle, and found that FM appeared to be on its way to becoming an established discipline.…”
Section: Methodology and Frameworkmentioning
confidence: 99%
“…Theoretically, it had hitherto been acknowledged by researchers in the field of FM (Nutt 1999) as a discipline in its early stages of development, hardly supported by adequate knowledge base and practical theory, and grossly under-researched. Although Junghans and Olsson (2014) are of the view that FM is characterised by its belonging to non-core business services focusing on workspaces and their management, recent indications point to the fact that it is now becoming a strategic function embedded within the strategic objectives of core business. It is also moving away from previous perception of it as being mainly technically oriented and reactive in nature (Bar-rett 2000;Grimshaw 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The available body of knowledge and the standardisation of terms and definitions, processes and measurement systems are indicators of a growing maturity of FM as a profession. Junghans and Olsson (2014) argued that according to six criteria for academic disciplines found in the literature, FM can also be recognised as an academic discipline: 1) FM has a particular object of research; 2) FM has an accumulated specialist body of knowledge; 3) FM has theories and concepts that can organise the accumulated specialist knowledge effectively; 4) FM has its own language i.e. it uses specific terminologies; 5) FM applies a number of research methods that fit with its research requirements; and 6) FM has some institutional manifestation in the form of subjects taught at universities or colleges and professional associations connected to it.…”
Section: Gustin 2003mentioning
confidence: 99%
“…While FM is characterised by its focus on non-core business services, workplaces and their management (Chotipanich, 2004;Junghans and Olsson, 2014), CREM has its foundation in the integration of asset management, general management, facility management and cost control (Krumm, 2001). Another difference is that CREM has its focus on real estate as a physical and economical asset utilized by an organization, while FM has a wider service focus including demands related to space and infrastructure as well as people and organisations (CEN, 2006a).…”
Section: Towards a Convergence Of Fm And Crem?mentioning
confidence: 99%